COLLECTION DEVELOPMENT PRACTICES AT THE UNIVERSITY OF BOTSWANA LIBRARY (UBL) - Madeleine, Fombad; Stephen M., Mutula (Malaysian Journal of Library and Information Science, 2003)
The paper discusses collection development practices at the University of Botswana Library that are largely influenced by subject librarians as the drivers of the collection development policy. The paper looks at the challenges facing the library’s collection development practices especially in relation to falling book budgets, proliferation of electronic materials, difficulties of dealing with faculty, poor book trade infrastructure, delays in the delivery of ordered books, and problems of evaluation of materials. The paper highlights strategies that the library is employing to deal with the challenges.